Health Status and Earnings of Migrant Workers from Rural China. (March 2015) - Qin, Lijian; Chen, Chien‐Ping; Liu, Xun; Wang, Chenggang; Jiang, Zhongyi
Abstract: The migration of rural laborers into cities for employment has been one of the main driving forces of China's economic growth over the past three decades. Based on a dataset collected by the Ministry of Agriculture of China from 2003 to 2007, this paper examines the impact of health on the earnings of migrant workers engaging in physically‐intensive work requiring good health. Our findings indicate that a poor health status not only weakens the incentive of rural laborers to participate in the migrant labor force but also significantly reduces their earnings. A migrant worker in poor health only earns 67 percent of what a healthy worker makes. Among all the human capital characteristics and family economic factors, health status is the most influential on earnings for less educated workers. Labor productivity has a greater impact on earnings than the annual number of days that a person works. Ongoing health‐care reforms aimed at the improvement of the health‐care services available to rural laborers are urged to help reduce poverty in rural China.